2021
DOI: 10.1021/acs.iecr.1c03062
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Properties of Photocatalysts via Nonthermal Plasma Modification: Recent Advances, Treatment Variables, Mechanisms, and Perspectives

Abstract: Surface modification is crucial in improving catalyst activity, since all catalytic reactions occur on the surface of the catalyst. This review discusses the application of nonthermal plasmas (NTP) for surface modification and functionalization of heterogeneous photocatalysts. NTP pretreatment provides an environmentally friendly and effective means for functionalization, surface etching, and/or defect regulation on the surface of photocatalysts. The correlations between modification variables and the properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…The gas pressure, which is positively correlated to the electron density, mainly affects the oscillation in plasma treatment. [ 36 ] Khaledian et al studied the operating pressure in Ar plasma for the treatment of rutile phase TiO 2 . [ 37 ] It was found that the decrease of pressure can subsequently enhance the velocity of Ar particles and the electrical field, resulting in more collision of the electrons with higher power to the TiO 2 surface.…”
Section: Operating Parameters In Plasma Treatmentsmentioning
confidence: 99%
“…The gas pressure, which is positively correlated to the electron density, mainly affects the oscillation in plasma treatment. [ 36 ] Khaledian et al studied the operating pressure in Ar plasma for the treatment of rutile phase TiO 2 . [ 37 ] It was found that the decrease of pressure can subsequently enhance the velocity of Ar particles and the electrical field, resulting in more collision of the electrons with higher power to the TiO 2 surface.…”
Section: Operating Parameters In Plasma Treatmentsmentioning
confidence: 99%
“…With the rapid development of renewable energy, CO 2 conversion and utilization become possible, with various methods investigated. The methods exploited include catalytic conversion, plasma conversion, plasma catalytic conversion, and others . Among these methods, the plasma conversions are promising.…”
Section: Introductionmentioning
confidence: 99%
“…The methods exploited include catalytic conversion, plasma conversion, plasma catalytic conversion, and others . Among these methods, the plasma conversions are promising. Plasma is defined as a fourth form of matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Vice versa, the NTP could be used to achieve surface functionalization, defect regulation, and surface etching on the surface of packing materials. 29 For instance, the type of discharge gases and processing parameters determine the discharge characteristics of NTP, which leads to various functional groups grafted on the surface of photocatalysts. 30 And the high-energy electrons/ions from ionization in the NTP result in surface defects on the photocatalysts to some extent.…”
mentioning
confidence: 99%